Current and future targeted therapies for non-small-cell lung cancers with aberrant EGF receptors. (March 2015) - Kanthala, Shanthi; Pallerla, Sandeep; Jois, Seetharama
ABSTRACT : Expression of the EGF receptors (EGFRs) is abnormally high in many types of cancer, including 25% of lung cancers. Successful treatments target mutations in the EGFR tyrosine kinase domain with EGFR tyrosine kinase inhibitors (TKIs). However, almost all patients develop resistance to this treatment, and acquired resistance to first-generation TKI has prompted the clinical development of a second generation of EGFR TKI. Because of the development of resistance to treatment of TKIs, there is a need to collect genomic information about EGFR levels in non-small-cell lung cancer patients. Herein, we focus on current molecular targets that have therapies available as well as other targets for which therapies will be available in the near future.